Інтегровані організаційні структури як основа інноваційного розвитку підприємств - Полозова, Т. В. (ХНУРЕ, 2016)
Проаналізовано теоретичні аспекти інте-граційних процесів промислових підприємств. Запропоновано як організаційну форму об'єднання підприємств – інтегрований промисловий блок. Theoretical aspects of integration processes of the industrial enterprises are analyzed. As the organizational form of association of enterprises of integrated industrial bloc is proposed. Such integrated structures will possess more powerful innovativ and investment capacity than individual enterprises, whose interaction is intended to increase efficiency through the manifestation of the synergetic effect which occurs as a result of integration processes.
Keywords: інновації; інноваційний розвиток; інтегрована організаційна структура; інтеграційний процес; інтегрована бізнес-група; інтегрований промисловий блок